Heart Rate Reactivity to Mental Stress in Athlete and Non-Athlete Children (Baltic Journal of Sport and Health Sciences, 2020)
Background. Research suggests that exercise training and/or physical fitness may be associated with lower heart rate reactivity and faster recovery from psychosocial stress. This relationship was rarely studied in children despite the potential protective role of physical activity in stress that may start in early life stages.Methods. In this laboratory investigation we examined 18 athlete and non-athlete children before, during and following exposure to mental stress which consisted of the Stroop Color Word Task and a mental arithmetic task, both distracted by classical music, in a counterbalanced research design.Results. The results based on absolute heart rate measures suggested that athletes exhibited lower heart rates in the stress-anticipation period as well as during the stress period than non-athletes. However, based on relative measures these differences vanished. The two groups of children did not differ in perceived arousal, perceived stressfulness of the mental tasks, and the self-reported feeling states before and after stress. Further, they did not differ in their performance on the two stress-eliciting active-coping tasks as indicated by the number of correct answers.Conclusion. These results appear to suggest that athletic status in children is unrelated to heart rate reactivity and other subjective psychological experiences before, during and after acute psychosocial stress. Keywords: adolescent, exercise, fitness, physical activity, relative measures.